ILLUMINATI(NG) THE SEARCH PROCESS: THEORIZING THE RESEARCH PRACTICES OF "ALTERNATIVE" OR "CONTROVERSIAL" RESEARCH - Eadon, Yvonne Melisande (AoIR Selected Papers of Internet Research, 2020)
Previous scholarship has examined how conspiracy theories spread online; addressed the question of what conspiracy theorists believe and why; asked whether or not conspiracy theorizing is a reasonable form of sense-making; and characterized the socio-cultural effects of conspiracy theories. Yet, the research practices of those who explore topics that have been labeled “conspiracy theories,” remain under-examined and under-theorized. Existing at the convergence of three interdisciplinary areas of scholarship—the study of conspiracy theory/ies, information seeking and behavior (e.g., research practices), and archival studies–this project will present preliminary dissertation research. The data will come from in-depth, qualitative interviews with individuals who regularly conduct research into one of three topics: the assassination of John F. Kennedy, the 1947 incident in Roswell, New Mexico, and the Missing 411 phenomenon. Interviews are semi-structured, addressing participants’ experiences of different modes of research: within a research community, in isolation (by themselves), and with the help of a reference archivist or librarian, among others that may emerge. This paper will also feature reflexive grounded theory analysis of my own feminist standpoint as a researcher and interviewer.